Impacts of COVID-19 pandemic on the global energy system and the shift progress to renewable energy: Opportunities, challenges, and policy implications - Hoang, Anh Tuan; Sandro Nižetić; Olcer, Aykut I.; Ong, Hwai Chyuan; Chen, Wei-Hsin; Chong, Cheng Tung; Thomas, Sabu; Bandh, Suhaib A.; Nguyen, Xuan Phuong (Energy policy, 2021)
Being declared a global emergency, the COVID-19 pandemic has taken many lives, threatened livelihoods and businesses around the world. The energy industry, in particular, has experienced tremendous pressure resulting from the pandemic. In response to such a challenge, the development of sustainable resources and renewable energy infrastructure has demonstrated its potential as a promising and effective strategy. To sufficiently address the effect of COVID-19 on renewable energy development strategies, short-term policy priorities should be identified, while mid-term and long-term action plans should be formulated in achieving the well-defined renewable energy targets and progress towards a more sustainable energy future. In this review, opportunities, challenges, and significant impacts of the COVID-19 pandemic on current and future sustainable energy strategies were analyzed in detail; while drawing from experiences in identifying reasonable behaviors, orientating appropriate actions, and policy implications on the sustainable energy trajectory were also mentioned. Indeed, the question is that whether the COVID-19 pandemic will kill us or provide us with a precious lesson on future sustainable energy development. •Two-faced impacts of COVID-19 pandemic on global energy system were evaluated.•Opportunities and challenges of the shift progress to clean energy were analyzed.•Drawn lessons, strategies for the future, and policy implications were mentioned.